PENGAWASAN PASAR NFT DI INDONESIA: PERLINDUNGAN HUKUM HAK CIPTA DAN MEKANISME PENYELESAIAN SENGKETA - Kartika, Fani Budi; Ihsan, Muhammad; Gunawan, Bambang Indra; Ilvira, Muhsin Lambok (Universitas Dharmawangsa, 2025)
The Non-Fungible Token (NFT) market has grown rapidly as one of the innovations in the digital economy, opening up new opportunities for creators to trade their works globally. However, this development also presents significant challenges related to copyright protection and dispute resolution in blockchain-based digital transactions. This study aims to analyze Indonesia's legal regulations in overseeing the NFT market, with a focus on copyright protection and dispute resolution mechanisms. The research method used is a normative juridical approach with a literature analysis of existing regulations, such as Law No. 28 of 2014 on Copyright. The results show that legal regulations in Indonesia have not fully accommodated blockchain technology and NFT transactions, thus creating legal loopholes that increase the risk of copyright infringement. In addition, the existing oversight and dispute resolution mechanisms are still conventional in nature, which is less effective for handling the complexity of the NFT market. To address these challenges, this study recommends the establishment of specific regulations governing copyright protection in the NFT market, the development of a technology-based surveillance system, and the implementation of a digital dispute resolution mechanism. The implication of this research is the importance of collaboration between the government, creator community, and technology platforms to create a healthy, safe, and competitive NFT market ecosystem. The findings are expected to be the basis for strengthening regulations and increasing legal protection on copyrighted works transactions in the NFT market in Indonesia.